Co-infections of two carbapenemase-producing Enterobacter hormaechei clinical strains isolated from the same diabetes individual in China. Issue 3 (2nd March 2021) - Ding, Manlin; Shi, Jiao; Ud Din, Ahmad; Liu, Yao; Zhang, Feiyang; Yan, Xiangjin; Li, Qin; Bai, JiaWei; Chen, Wenbi; Zhou, Yingshun
Abstract : Introduction. Since mcr-1 was first reported in China, there have been ten variants of MCR appearing nationwide so far. Multidrug-resistant Enterobacteriaceae bacteria carrying both NDM and MCR have become a serious threat to global public health. Hypothesis/Gap Statement. The genetic structure of mcr-9 needs to be better understood in order to better prevent and control the transmission of drug-resistant genes. Aims. The aim of this study was to characterize the presence of two Enterobacter hormaechei isolates, which carries bla NDM-5 CME2 and the coexistence of mcr-9 and bla NDM-1 strain CMD2, which were isolated from a patient with diabetes in Sichuan, China. Methodology. The microbroth dilution method was used for antibiotic susceptibility. Conjugation experiment was used to investigate the transferability of bla NDM-1, bla NDM-5 and mcr-9 . Whole-genome sequencing was performed on Illumina HiSeq platform. The ability of biofilm formation was detected by crystal-violet staining, the virulence of the bacteria was measured by Galleria mellonella killing assay. Results. bla NDM-5 carrier CME2 and CMD2 with bla NDM-1 and mcr-9 were resistant to carbapenems, β-lactam, aminoglycoside, quinolone and tetracycline, while CMD2 was also resistant to colistin. Conjugation assay and plasmid replicon typing further demonstrated that both bla NDM-1 and bla NDM-5 were respectively present on the self-transferrable IncX3 plasmid, mcr-9 was located on the self-transferrable IncHI2 plasmid. Through the analysis of mcr-9 gene context, the structure was DUF4942-rcnR-rcnA-copS -IS 903-mcr-9-wbuC-qseC-qseB-IS1R -Δ silR -IS 903, bla NDM-1 context was IS 3000 -ΔIS Aba125 -IS 5-bla NDM-1 - ble-trpF-groS-groL-insE -ΔIS 26 structure, bla NDM-5 structure was IS 3000-bla NDM-5 - ble-trpF-dsbC -ΔIS 26-umuD -IS Kox3-tnpR-parA . Biofilm formation of CME2 was stronger than CMD2. There was no significant difference in virulence between the two strains. Conclusion. This study reveals two multiple drug-resistant E. hormaechei isolates from diabetes patient samples. E. hormaechei carrying two NDM-resistant genes is already a serious threat, where MCR is an important cause of treatment failure in bacterial infections. This study is a reminder not only to prevent infection in patients with diabetes, but also to constantly monitor the epidemic and spread of the drug-resistant gene.